Percutaneous Endovascular Sapheno‑Femoral Bypass for Treatment of Chronic Iliac Vein Stent Occlusion - Osman S. Ahmed; Roberto Santos Loanzon; Bulent Arslan (The Arab Journal of Interventional Radiology, 2018)
We report a case of a 45-year-old female with a history of chronic iliac vein and inferior vena cava (IVC) occlusion, who presented with diffuse bilateral lower limb edema and pain secondary to severe postthrombotic syndrome. Computed tomography and digital subtraction angiography demonstrated reocclusion in the patient's previously placed iliofemoral and IVC stents. Recanalization was achieved with a percutaneous endovascular bypass approach after unsuccessful attempts using standard and other advanced endovascular techniques including sharp needle and radiofrequency wire recanalization.